Short-term low-volume high-intensity intermittent training improves judo-specific performance - Franchini, Emerson; Julio, Ursula Ferreira; Gonçalves Panissa, Valéria Leme; Lira, Fábio Santos [UNESP]; Agostinho, Marcus Fabio; Branco, Braulio Henrique Magnani (My University, 2017)
Background & Study Aim: An important aspect concerning the specificity principle is related to the time structure of the sport. The aim of our study was the effects of short-term low-volume high-intensity intermittent training (HIIT) added to traditional judo training on physiological and performance responses to judo-specific tasks. Material & Methods: Thirty-five judo athletes were randomly allocated to a control group (n = 8) and 3 HIIT groups: (1) lower-body cycle-ergometer (n = 9); (2) upper-body cycle-ergometer (n = 9); (3) uchi-komi (technique entrance) (n = 9). All protocols were constituted by 2 blocks of 10 sets of 20 s of all-out effort, with 10 s interval between sets and 5 min between blocks, executed twice per week for 4 weeks. Pre and post-training the athletes performed the Special Judo Fitness Test (SJFT) and a match simulation, with blood lactate, hormones (cortisol, C, and testosterone, T) and muscle damage marker (creatine kinase, CK, lactate dehydrogenase, LDH, aspartate aminotransferase, AST and alanine aminotransferase, ALT) measurements. Results: There was an increase (p = 0.031) in the number of throws in the SJFT for the upper-body group, while decreasing the HR immediately after the SJFT and the number of sequences in standing position for the lower-body group (p < 0.001 and p = 0.034, respectively), the index in the SJFT for the uchi-komi group (p = 0.015) and the CK concentration (p = 0.014) in the match simulation for the upper-body group. T/C ratio increased (p = 0.028) after the match simulation in the post-training. Conclusion: All training modes improved performance, biochemical and hormonal response to judo-specific performance, but each group adapted in a different way.
Keywords: Athletes; Combat sport; Training intensity; Training load; Uchi-komi